Global logistics networks as an imperative for the sustainable development of the world economy - Kotov, Tymofiy (Herald of Economics, 2025)
Introduction: Global logistics networks are a fundamental component of the global economy, ensuring the effective movement of goods and services on an international scale. This paper examines the main types of logistics networks, their role in ensuring sustainable development, and innovative approaches to optimizing logistics processes. Particular attention is given to the challenges facing logistics in the context of globalization and potential solutions to these challenges. Objective of the Study: The primary objective of the study is to conduct a systematic analysis of global logistics networks with a focus on their role in ensuring the sustainable development of the global economy. This includes assessing the effectiveness of various types of logistics networks and identifying innovative approaches that can enhance their efficiency and environmental sustainability. Research Methods: A systematic approach has been employed to comprehensively analyze logistics networks, considering their structural characteristics and functional capabilities. Comparative analysis methods were used to assess the effectiveness of different types of transport modes within logistics networks, and forecasting methods were applied to determine future trends in the industry. Summary: The paper discusses the current state and development trends of global logistics networks, which play a crucial role in ensuring the sustainable development of the global economy. It analyzes the main types of logistics networks, including maritime, air, rail, and road transportation, with a focus on their efficiency, environmental impact, and adaptability to new challenges. The role of information technology and innovations in enhancing logistics process efficiency is also highlighted. Research Results: Global logistics networks play a significant role in ensuring the effective movement of goods and services internationally. These networks are essential for the sustainable development of the global economy, as they contribute to increased trade volumes and improved competitiveness of countries. The development of logistics networks is a key factor in ensuring the efficient functioning of international trade, creating new markets, and improving living standards. These networks facilitate the rapid and efficient movement of goods from production centers to end consumers worldwide. To achieve this, global logistics networks utilize various transportation modes, including maritime, air, rail, and road transport. Additionally, modern information technologies and management systems are employed to optimize routes, track cargo, and plan logistics operations. Future Prospects: Future research should focus on the development and testing of new models for integrating various types of transport within global logistics networks, with an emphasis on implementing advanced technologies such as artificial intelligence and blockchain. Furthermore, an important area of focus should be the analysis of the impact of environmental innovations on the efficiency and sustainable development of logistics processes. Specifically, it is important to explore how emerging green technologies can contribute to reducing emissions and enhancing the overall ecological sustainability of logistics systems.